Cryptanalysis of Novel Image Encryption Scheme Based on Multiple Chaotic Substitution Boxes - Ammar S. Alanazi; Noor Munir; Majid Khan; Muhammad Asif; Iqtadar Hussain (IEEE Access)
In current years many chaos-based Substitution boxes (S-boxes) have been proposed. Recently, an image encryption technique based on multiple chaotic S-box was offered. This encryption method was based on the concept of confusion only produced by the implementation of the S-box. The concept of confusion utilized in the understudy technique can be smashed by using just one chosen-plaintext attack and a chosen-ciphertext attack. This article presents a detailed structure of two types of cryptographic attacks on the diffusion-based encryption scheme. The proposed attacks are successfully performed to retrieve the key with very little execution time by using just one chosen image which indicates the vulnerability of multiple chaotic S-boxes-based cryptosystems. The retrieved data is passed through some statistical analysis such as correlation, histogram, and entropy to check the correctness of recovered data.